Violent Aggression Exposure, Psychoemotional Distress, Aggressive Behavior, and Academic Performance Among Adolescents - Evans, Joyce Renee (2017)
Sixty percent of youth indicate exposure to violence. Such exposure is a noted risk factor for youths' well-being, including cognitive, emotional, and behavioral development. However, there is a gap in the literature regarding whether exposure to violence predicts impaired academic performance. The purpose of this quantitative study was to test a model with cognitive, behavioral, and emotional sequelae of exposure as mediators of the relationship between exposure to violence and academic performance among adolescents who are at risk for exposure and attend inner-city high schools. Ninety-nine students, primarily female and African-American, in Grades 10 to 12 at two public schools in a major mid-Atlantic metropolitan district completed self-report measures for exposure to violence, aggressive behavior, aggressive cognitions, psychoemotional distress, and academic performance. A series of linear regressions was used for mediational analysis. Path coefficients were interpreted to test the proposed causal model. Consistent with previous research, a weak, but statistically significant bivariate relationship was found between exposure and grade point average (GPA). However, the relationship was indirect, mediated by students' aggressive cognitions: Higher levels of aggressive cognitions provided the best predictors of negative relationships exposure to violence with GPA. These findings have important social change implications. In particular, findings suggest that educators, parents, and mental health professionals can strengthen academic performance among adolescents with higher academic potential who are exposed to violence by offering support for positive coping styles and alternatives to attitudes that normalize aggression